A Study on Graph Theory and Its Application (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The main purpose of this paper is to present the main principles of Graph theory and analysis regarding linked graph, Eulerian graph, Hamiltonian graph etc. Graph analysis is a theory of mathematics which has wide application in the field of mathematics as well as in other branches of research. This paper intends to highlight the uses of graph theory in our everyday life, in Computer science, Operation Research.